Investigation and experiment of radar systems in unmanned arial vehicles-VII - Mainisah Buang. (2013)
In the recent years, there are many new invention or creation of engineering products such as sensors, measurement devices and data acquisition modules. One of the newest data acquisition modules which had been selling in the market is a module called DT9837C. Data Translation releases DT9837C dynamic signal acquisition module for USB on the 25th May 2011[20].